Endogenous complement-activating IgM is not required for primary antibody responses but promotes plasma cell differentiation and secondary antibody responses to a large particulate antigen in mice - Palm, Anna-Karin E.; Westin, Annika; Ayranci, Diyar; Heyman, Birgitta (Frontiers in Immunology, 2024)
Lack of complement factor C1q of the classical pathway results in severely impaired primary antibody responses. This is a paradox because antibodies, especially IgM, are the most efficient activators of the classical pathway and very little specific IgM will be present at priming. A possible explanation would be that natural IgM, binding with low affinity to the antigen, may suffice to activate complement.In support of this, mice lacking secretory IgM have an impaired antibody response, which can be rescued by transfer of non-immune IgM. Moreover, passive administration of specific IgM together with antigen enhances the antibody response in a complement-dependent fashion. To test the idea, we have used a knock-in mouse strain (C13) carrying a point mutation in the IgM heavy chain, rendering the IgM unable to activate complement. Mutant mice backcrossed to BALB/c or C57BL/6 background were primed and boosted with a low dose of sheep red blood cells. Confirming earlier data, no impairment in early, primary IgM-or IgG-responses were seen in either of the C13 strains.However, in one of the mutant strains, late primary IgG responses were impaired. A more pronounced effect was observed after boost, when the IgG response, the number of germinal center B cells and antibody secreting cells as well as the opsonization of antigen were impaired in mutant mice. We conclude that complement activation by natural IgM cannot explain the role of C1q in primary antibody responses, but that endogenous, specific, wildtype IgM generated after immunization feedbackenhances the response to a booster dose of antigen. Importantly, this mechanism can only partially explain the role of complement in the generation of antibody responses because the IgG response was much lower in C3-or complement receptor 1 and 2-deficient mice than in C13 mice.